Impact of oral microbiota on radiation-induced oral mucositis: A single-arm prospective study - LU Zhiyuan, XU Yimin, ZHOU Mengyuan, LU Yang, WEI Zhihao, XIAO Can (Editorial Office of Stomatology, 2024)
Objective To investigate dynamic shifts in the oral microbiota and their association with the progression and aggravation of radiotherapy-induced oral mucositis(RIOM) in patients with head and neck malignancies undergoing radiotherapy. Methods Based on 16S rRNA gene sequencing, dynamic changes of oral microbiota in patients was analyzed. Results Firmicutes, Bacteroidetes, and Actinobacteria consistently constituted the predominant bacteria in the oral cavity. While there were no significant changes in the absolute abundance of microbiota, there were notable alterations in their relative richness and evenness. Analyses including CCA/RDA and Kruskal-Wallis indicated a significant increase in the proportions of Streptococcus and Lactobacillus genera in the later stages post-radiotherapy, showing statistically meaningful differences. Conclusion RIOM is associated with dysbiosis of oral microbiota. Microbial dysbiosis may aggravate the severity of RIOM. Streptococcus and Lactobacillus could be closely related to the progression of RIOM, pending further validation through animal experiments.